Fellow and training director perspectives on personal leaves during fellowship training in neuropsychology and considerations for best practice. Issue 4 (19th May 2023) - Shapiro, Danielle N.; Anderson, Carolyn; Gragert, Marsha N.; Johnson, Abigail; Heffelfinger, Amy
Abstract: Objective: Management of personal leaves represents an important component of diversity, equity, and inclusion (DEI) initiatives. This study aims to understand the ways in which both training directors and fellows in neuropsychology training programs understand, perceive, communicate about, and plan for personal leaves during fellowship training. We also aim to provide empirically based recommendations for training directors communicating with fellows about personal leaves. Method: Training directors ( N = 40) and postdoctoral fellows ( N = 51) were recruited to complete surveys examining their knowledge and perspectives on personal leaves through a professional listserv. Results: While most training directors reported that their programs offer paid personal leave options, a substantial minority did not. There were discrepancies between training directors' and fellows' knowledge about leave policies and perceptions of the professional implications of taking a personal leave, such that fellows reported less knowledge and a greater perception that taking a leave during training may have a negative professional impact. Conclusions: Findings suggest that training directors in neuropsychology should clearly communicate institutional leave policies early in, or even before the start of, the fellowship period and work to cultivate a culture of openness around both broad issues of work-life balance and specific issues related to personal leaves with trainees.